The Utility of the helicobacter pylori stool antigen test in managing dyspepsia: an experience from a low resource setting - Lule Segamwenge, Innocent; Kagimu, Magid; Ocama, Ponsiano; Opio, Kenneth (African health sciences, 2014)
Dyspepsia is defined as a chronic or recurrent pain or discomfort centered in the upper abdomen. Endoscopy is the best strategy for confirming the cause of dyspepsia. Non- invasive strategies would be more appropriate in low resource countries where endoscopy is not readily available. However, there is concern that these strategies may miss serious disease like gastric cancer. One test that needs to be assessed in this regard is the Helicobacter pylori stool antigen test (HPSAT). Objective: To determine the validity of the stool antigen test in predicting H. pylori associated disease among patients with dyspepsia. Methods: In this prospective study patients with dyspepsia attending Mulago Hospital were recruited consecutively. Helicobacter pylori was determined using the Rapid Strip HpSA ®, endoscopy and gastric mucosal biopsy were done. Results: 167 patients with dyspepsia were recruited into the study. There were ninety six (57.5%) females and seventy one (42.5%) males with an average age of 48.1(±18.1) years. Patients presenting with dyspepsia in Mulago hospital were more likely to come from the Central 60 (36%) and western tribes 55 (33%). The commonest endoscopic finding was oesophagitis 25 (15%). Peptic ulcer disease was found in 32 (19.2%) and 54 (32.3%) had normal endoscopy findings. H pylori was found in 33.5% and 32.5% using the HPSAT and histology respectively. The validity of the HPSAT in predicting H.pylori associated diseases was generally low with an overall sensitivity of 55.8%, and specificity of 74.2%. However, the validity was higher in predicting the diagnosis of peptic ulcer disease with a sensitivity 59.4% and specificity 72.6%. Conclusion and recommendations: The HPSAT may be used in the test and treat strategy for young patients with dyspepsia without alarm signs and symptoms in low resource settings. However, because of its low validity in predicting H.pylori associated disease, it is important to follow up patients so that if symptoms persist or recur endoscopy is performed Keywords: helicobacter pylori, stool antigen, dyspepsia, low resource setting
Keywords: Helicobacter pylori; Stool antigen; Dyspepsia; Low resource setting